The role of power and trust for successful information sharing in the supply chain - Sylvia Mardiana (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The supply chain is a series of operations consisting of interconnected units both within and outside the company such as suppliers, producers, and distributors, each of which holds information at a different level. These parties need to be coordinated using information sharing as a coordination mechanism. Information sharing enables them to make the right and quick decisions that can improve the performance of the supply chain. Information sharing has received a lot of attention from researchers who analyze it from different perspectives. However,  no research shows the relationship between factors that drive information sharing to succeed. This study produces a model of power, trust, and information sharing.